Surgical treatment of complicated forms of erysipelas - L. A. Vasylevska (Сучасні медичні технології)
Purpose of the study. The goal of the article is to find out the frequency of complicated forms of erysipelas among the general population of the disease and to determine the main directions for their surgical treatment.